(untitled) (Sains Humanika, 2018)
Conveying greetings to non-Muslims and replying greetings uttered by them are the issues that affect the sensitivity of Muslims in Malaysia. Since Malaysia is a plural-society nation, there are non-Muslims who are always intermingled with the Muslims and are impressed with some of Muslim cultures. And when this happens, it raises many questions such as is it allowed for Muslims to say â€œAssalamualaikumâ€ to non-Muslims? Is it obligatory to return greetings given by non-Muslims? How to greet people in a ceremony consisting of Muslims and non-Muslims? Is it permissible to say "Good Morning" or "Good Evening" to non-Muslims? Therefore, this paper will explore the views of Muslim scholars in each of these issues so that readers can clearly understand the Islamic view on this issue. Analytical and critical methods will be utilized when elaborating the view of scholars in this issue. The conclusion of this study is that Muslims are not allowed to greet non-Muslims with the word â€œAssalamuaâ€™laikumâ€. However, if non-Muslims start to greet with the word â€œAssalamuaâ€™laikumâ€ then Muslims can reply it with the word â€œWa’alaikumussalamâ€. While other greeting of speech other than the remarks of â€œAssalamu’alaikumâ€ is permissible.